Satellites, Self-reports, and Submersion: Exposure to Floods in Bangladesh - Guiteras, Raymond; Jina, Amir; Mobarak, A. Mushfiq (American Economic Review, 2015)
A burgeoning “Climate-Economy” literature has uncovered many effects of changes in temperature and precipitation on economic activity, but has made considerably less progress in modeling the effects of other associated phenomena, like natural disasters. We develop new, objective data on floods, focusing on Bangladesh. We show that rainfall and self-reported exposure are weak proxies for true flood exposure. These data allow us to study adaptation, giving accurate measures of both long-term averages and short term variation in exposure. This is important in studying climate change impacts, as people will not only experience new exposures, but also experience them differently.